PRODUKSI DAN KUALITAS SEMEN SAPI PEJANTAN SIMMENTAL DI BALAI INSEMINASI BUATAN LEMBANG PADA BERBAGAI WAKTU PENAMPUNGAN (Semen production and qualty of simmental bulls in lembang artificial insemination center at different collection time) - Ardita, Dira; Herawati, Ervi; Salamah, Aisyatus (JURNAL NUKLEUS PETERNAKAN, 2024)
The semen of Simmental bull is widely used for artificial insemination. The purpose of this research was to determine the most ideal semen collection time to obtain the best production and quality of Simmental bull semen. The materials used were fresh semen from 11 Simmental bulls collected at various times between 07.00-09.00 WIB and 09.00-11.00 WIB. The method used in this study was a case study utilizing data from semen collection in July 2023 based on records of semen production and quality of Simmental bulls at the Lembang Artificial Insemination Center. The observed parameters were macroscopic characteristics such as volume, color, pH, consistency, frozen semen production (straw), and microscopic characteristics such as concentration, motility, and post-thawing motility (PTM) of frozen semen. The results showed that different semen collection times affect the volume and production (straw) obtained, but there was no effect on color, pH, consistency, concentration, motility, and post-thawing motility (PTM) parameters. The conclusion of this study is that the semen collection time from 07:00 to 09:00 AM WIB results in better volume and production (straw) of frozen semen compared to the collection time from 09:00 to 11:00 AM WIB